2022
DOI: 10.2147/ccid.s379609
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome in Comedonal Contents of Inflammatory Acne Vulgaris is Composed of an Overgrowth of Cutibacterium Spp. and Other Cutaneous Microorganisms

Abstract: Background Acne vulgaris (acne) and cutaneous resident microorganisms are considered to be closely related. However, the bacterial and fungal microbiota in the comedonal contents of inflammatory acne lesions have not yet been investigated in detail. Purpose To clarify the relationship between cutaneous microorganisms and acne, we examined the microbiome in the comedonal contents of inflammatory acne and on the facial skin of patients with acne using 16s rRNA and ITS gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…They found that Malassezia restricta and Staphylococcus epidermidis might play the same important role as Cutibacterium acnes in the development of inflammatory lesions in acne patients due to they have the similar proliferation trends. Notably, the same findings were also reported in a recent study that detect the skin microorganisms of Japanese acne subjects ( Akaza et al, 2022 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…They found that Malassezia restricta and Staphylococcus epidermidis might play the same important role as Cutibacterium acnes in the development of inflammatory lesions in acne patients due to they have the similar proliferation trends. Notably, the same findings were also reported in a recent study that detect the skin microorganisms of Japanese acne subjects ( Akaza et al, 2022 ).…”
Section: Introductionsupporting
confidence: 88%
“…Body site is one of the important factors influencing the composition of skin microbiota, its impact is even higher than ethnicity in some reports ( Perez Perez et al, 2016 ). Although there were reports that obtain samples from different acne sites, most of them just paid attention to facial acne or lack detailed reports because of too less samples for each site ( Kim et al, 2021 ; Shi et al, 2021 ; Akaza et al, 2022 ). Thus, it is deserved to systematically investigate the structural characteristics of the skin microbiota in different acne areas and to excavate the biomarkers of sampling sites.…”
Section: Discussionmentioning
confidence: 99%
“…The skin sebum is an important component of the skin barrier and plays a critical role in maintaining skin moisture, reducing TEWL, protecting the skin against the external environment (e.g., ultraviolet (UV) light), and sustaining skin barrier function 17–20 . Additionally, the sebum content influences the skin microbiome, which could adversely affect skin conditions and lead to inflammation and skin disorders 21 . Therefore, the sebum level is an important parameter widely used in clinical diagnostics and cosmetic applications 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, even now, with a lot of pieces of knowledge about the pathogenesis of acne, the exact cause has yet to be discovered. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…However, even now, with a lot of pieces of knowledge about the pathogenesis of acne, the exact cause has yet to be discovered. 1,2 Malassezia folliculitis (MF) results from an overgrowth of Malassezia yeasts, which are normal skin flora. The abnormal proliferation of yeast can cause inflammation of the hair follicles by two possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%